Blood Profile of Wistar Rats due to Subcronic Condition Caused by Sodium Nitrite - Dyah Ayu Widyastuti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract Nowadays, chemicals used as food additives are increasing. One of the chemicals commonly used is sodium nitrite (NaNO2 ). Sodium nitrite is found in sausage and another meat product. Sodium nitrite is used as food preservative agent. But, the presence of NaNO2 can influence blood cells ability to carry oxygen. It causes anemia and forms nitrosamines, carcinogenic agents. This research is purposed to know blood profiles of Wistar rats on subchronic condition caused by NaNO2 . The research was done for 3 months as subchronic time. Twenty seven Wistar rats were divided into 3 groups, control group (K), first group (P1) treated by NaNO2 with dose of 11,25 mg/kg bodyweight/day, and second group (P2) treated by NaNO2 with dose of 22,50 mg/kg bodyweight/day. Blood samples were collected from orbital sinus and tested once a week for hematological parameters, including white blood cells (WBC), red blood cells (RBC), hemoglobin (Hb), hematocrit (HCT), lymphocyte level, and neutrophil level. The data were analyzed with ANOVA using SPSS 16 program for Windows and the blood profiles alteration were seen. The results from this study showed there were no significant differences among the blood profiles of Wistar rats treated by NaNO2 with dose of 11,25 mg/kg 2 bodyweight/day and dose of 22,50 mg/kg bodyweight/day compared to that of the control group, except WBC values at subchronic condition at dose of 22,50 mg/kg bodyweight/day which decreased 23,46%. The NaNO 2 could not influence the blood profiles of rats treated by NaNO2 subchronically.